Redescription of Gobio nigrescens from the Hari River drainage (Teleostei: Cyprinidae) - Mousavi-Sabet, Hamed; Ganjbakhsh, Babak; Geiger, Matthias F.; Geiger, Matthias F.; Freyhof, Jörg (Zootaxa, 2016)
Gobio nigrescens, from the Hari River drainage, is redescribed. It represents a valid species distinguished from congeners in the adjacent Caspian and Aral Sea basins by a combination of characters: a naked breast, 16 circumpeduncular scales and 6–7 irregularly shaped, black or brown blotches on back behind dorsal-fin base.